Achieving refined microstructure and enhanced mechanical properties in a Ti-46Al-5Nb-0.1C alloy via in-situ co-precipitation of multi-phase reinforcements - Weigang Yang; Dingbang Sun; Yongfeng Liang; Mingao Li; Wenjing Li; Junpin Lin (Materials & Design)
A novel TiAl composite with multi-phase reinforcements has been successfully prepared by combination of plasma rotating electrode process, low-energy ball milling and induction hot-press sintering in the present study. The introduction of multi-phase reinforcements significantly refined the lamellar colonies and enhanced the mechanical properties of TiAl composites. With the addition of B4C, nano TiB, nano Ti2AlC, and TiB whiskers precipitated at the boundaries of lamellar colonies, collectively forming a network-like reinforcement structure. Meanwhile, the mean grain size of (α2 + γ) lamellar colonies decreased significantly from 425.3 μm to 78.5 μm with 0.1 wt.% B4C addition. In addition, TiAl composites with 0.05 wt.% and 0.1 wt.% B4C achieved UTS and elongation of 637.68 ± 29.13 MPa/0.24 ± 0.12 % and 659.85 ± 35.47 MPa/0.09 ± 0.05 % (room temperature), as well as 591.19 ± 27.95 MPa/1.76 ± 0.44 % and 553.85 ± 36.34 MPa/1.47 ± 0.39 % (800 °C), respectively. The addition of B4C refined the lamellar colonies, mitigated stress concentration, leading to a more homogeneous distribution of dislocations within the microstructure. Simultaneously, the introduction of multi-phase reinforcements in TiAl composites induced substantial nano twins during deformation, thereby effectively alleviating stress concentration and enhanced its plasticity.